PENINGKATAN KINERJA PELABUHAN KRUENG GEUKUEH, LHOKSEUMAWE, PROVINSI NANGGROE ACEH DARUSSALAM - Tjeendra, Melinda; Joewono, Tri Basuki; Santosa, Wimpy (Jurnal Transportasi, 2008)
AbstractÂ Sea transportation sector comes to be one golden bridge for Indonesia to increase the economy activity. In this context, Nanggroe Aceh Darussalam Province is one of the strategic provinces, which acts as a gate to enter in western part of Indonesia. Being surrounded by sea, a harbor and sea transportation in NAD is a must. One of the most important harbour in NAD province is Krueng Geukueh Harbour. NAD has very strategic position, between Malaysia and Singapore, and potential conditions, e.g. closely related with central business district, the existence of abundance natural resources, and the availability of airport. The purpose of this study is to improve the performance of Krueng Geukueh Harbour. An improvement efforts suggested include, improving unity of intermodal and multimodal in this harbour, increasing harbourâs capacity of facilities, increasing shipping safety, improving human resources quality and technology usage, and offering opportunities for investor.Â Keywords: harborâs performance, intermodal transportation, multimodal transportation.